Trends in worldwide asthma prevalence - Asher, M Innes; García-Marcos, Luis; Pearce, Neil E; Strachan, David P (The European respiratory journal, 2020)
This review of trends in worldwide asthma prevalence starts with defining how asthma prevalence is measured in populations and how it is analysed. Four population studies of asthma across at least two regions are described: European Community Respiratory Health Survey (ECRHS), the International Study of Wheezing in Infants (EISL), the International Study of Asthma and Allergies in Childhood (ISAAC) and the World Health Survey (WHS). Two of these (ISAAC and WHS) covered all the regions of the world; each using its own standardised questionnaire-based methodology with cross-sectional study design, suitable for large populations. EISL (2005 and 2012) and ISAAC (1996-1997 and 2002-2003) have undertaken a second cross-sectional population survey from which trends are available: EISL in three centres in two countries; ISAAC 106 centres in 56 countries (13-14 year olds) and 66 centres in 37 countries (6-7 year olds). Key results from these studies are presented. Unfortunately, there is no new worldwide data outside of EISL since 2003. Global Burden of Disease estimates of asthma prevalence have varied greatly. Recent reliable worldwide data on asthma prevalence and trends is needed; the Global Asthma Network Phase I will provide this in 2021.